The Influence and Legacy of the Shepherding Movement on the Current Neo-Pentecostal Movement in South Africa - Resane, K. Thomas (Journal for the study of religion, 2021)
This essay focuses on the history, theology, and demise of the Shepherding movement, a discipleship network pioneered by five teachers, Charles Simpson, Bob Mumford, Derek Prince, Don Basham, and Ern Baxter, based in Fort Lauderdale, Florida, USA. These leaders aimed to provide meaning and order through house churches and cell groups to address the spiritual maturity of the Charismatic believers. Some key concepts of the Shepherding movement that impacted the Neo-Pentecostals will be discussed, namely submissions to authority; male leadership; ecclesiology; pastoral training and formation; and church polity, emphasizing the apostolic and prophetic ministries. The second part of the essay highlights the current Neo-Pentecostal movement and how it has taken over the legacy of extra-biblical revelation from the Shepherding movement. This reveals the influence that the Shepherding movement has left, after it has been inherited by the Neo-Pentecostal movement.